Ductile and Gray Cast Irons Deterioration with Time in Various NaCl Salt Concentrations - Sami A. Ajeel; Safaa Mohommed Hasoni (Engineering and Technology Journal, 2008)
Gray cast iron is used in wide engineering applications especially pipesand these pipes are exposed to failure in most cases so that ductile cast iron is usedinstead of it later.This project deals with the study of microstructure characteristics andchemical analysis for both materials in order to use them in the analysis of themicrostructure after the corrosion tests involving immersion, polarization indifferent sodium chloride concentrations (0.01%, 0.58% and 3.5% NaCl).Immersion results indicate that the corrosion resistance of both types ofcast irons is excellent and ductile iron is better than gray cast iron and thereduction in corrosion rates for both materials is related to barrier layer depositedon the surface which is more uniform on ductile iron surface.The electrochemical tests involve measurement of corrosion potential inopen circuit using the same solutions for both materials and potentiostatic test isused to measure cathodic and anodic polarization in the above solutions. The teststarted from cathodic region to the anodic region with sweep rate of 10 m V/min toobtain the general behavior and measure the polarization parameters for bothmaterials.The measured corrosion potentials of the open circuit in all solutions aremore noble values for gray iron than that for ductile iron. Corrosion potentials onpolarization measurements point out to the same indication but the ability tostart and form barrier layer in ductile is better than in gray iron.Microstructure observations after the electrochemical tests indicatethe presence of uniform layer on ductile surface and graphitization process isobtained on gray iron.